Molecular Insights into Triazole Resistance: A Comprehensive Review on Active Site Tyrosine Mutations in Fungal 14 Alpha-Demethylase - Babriwal, Gourav (International Journal of Pharmaceutical & Biological Archive, 2024)
Background: Triazoles are essential antifungal agents used in clinical and agricultural contexts to manage fungal infections. However, their efficacy is increasingly compromised by the emergence of resistant fungal strains. A key mechanism of resistance involves mutations in the lanosterol 14 Alpha-demethylase enzyme (CYP51), particularly at conserved residues such as the active site tyrosine. These mutations disrupt triazole binding, leading to reduced antifungal susceptibility. Objective: This review provides a detailed examination of the molecular mechanisms underlying triazole resistance, with a focus on mutations affecting the conserved active site tyrosine in fungal CYP51. It discusses structural insights, clinical implications, and potential strategies to counteract resistance. Key Findings: The active site tyrosine in CYP51 plays a critical role in maintaining enzyme function and facilitating triazole binding. Mutations in this residue alter the enzyme’s structure, reducing the binding affinity of triazoles and conferring resistance. These mutations are prevalent in both clinical and agricultural fungal strains, posing significant challenges for treatment and crop protection. Advances in structural biology and molecular diagnostics have enhanced our understanding of these mutations, enabling better monitoring and potential drug development. Conclusion: Active site tyrosine mutations represent a pivotal mechanism in triazole resistance, emphasizing the need for novel therapeutic approaches. Targeted drug design and combination therapies hold promise in overcoming resistance and safeguarding triazole efficacy. This review highlights the importance of continued research and global surveillance to mitigate the impact of antifungal resistance.